Assessing the Knowledge, Attitude, and Practices of Cigarette Smokers and Use of Alternative Nicotine Delivery Systems in Pakistan: A Cross-Sectional Study - Abdul Hameed; Daud Malik (Advances in Public Health)
Background. This research has been conducted to assess smokers’ knowledge and behavior vis-à-vis combustible smoking cessation, prevalence, and risk, and the use of alternative nicotine delivery systems to quit smoking. Methods. A mixed-method approach utilizing cross section primary survey data and comprising descriptive and s-KAP index analysis has been adopted to ascertain the relationship between dependent and independent s-KAP variables; the principal component analysis methodology has been used to determine the use of alternative nicotine delivery systems. Results. Most of the smokers were aged between 15 and 35 years. A predominant 69.8% of the smokers came from middle-class background. Moreover, 71.3% were unaware of any alternative Tobacco Harm Reduction product. A majority of the respondents (68.2%) were keen to quit smoking. However, when asked why they had not succeeded, 52.9% reported addiction to nicotine as the main impediment. In Pakistan, lack of smoking cessation services is the weak link in the fight against the tobacco epidemic. Smokers are generally unaware of the Tobacco Harm Reduction products available in Pakistan; moreover, only 10.9% of the respondents were willing to spend more than Rs. 4000 per month on Tobacco Harm Reduction products. The average s-KAP score for young adults below the age of 20 was much lower than the national average but improved with the level of education. Interestingly, the score of smokers who had ever tried to quit smoking was slightly higher than that of those who had never tried to quit. Conclusion. There is intent to quit combustible smoking but the policy and infrastructure necessary for successful quitting are missing. Pakistan needs to concentrate on two fronts: a large scale awareness campaign against the use and harms of combustible smoking and simultaneously providing affordable and accessible smoking services across the country. Pakistan should look at the use and regulation of safer nicotine products in the UK. The country should carefully weigh the options of ensuring how to incorporate the use of safer nicotine delivery systems in its tobacco control efforts.